Evaluation of Risk-Based Communication Management in Design-Build Building PT XYZ Projects to Improve Time Performance - Jariski, Muzamil; Isvara, Wisnu; Riantini, Leni Sagita (Al-Makki Publisher, 2025)
The design-build concept continues to evolve as a delivery method in the global and Indonesian construction markets. This study, conducted at PT XYZ, reveals that all design-build building projects over the past three years (2022–2024) have experienced delays or schedule extensions in execution. One of the main factors contributing to poor time performance in design-build projects is communication-related issues. The objective of this study is to evaluate communication management in design-build projects based on dominant risks. This research was conducted by collecting data through literature review, archival analysis, and expert validation questionnaire surveys. The study identified 4 phases, 12 stages, and 58 activities involving 9 stakeholders, which encompassed 59 communication activities and 40 communication-related risks were identified and further analyzed using statistical methods and subsequently evaluated based on their risk levels in order to plan risk responses in communication management evaluation to enhance time performance in design-build building projects.